Analisis Kinerja Topologi WSN Untuk Aplikasi Kelembapan Tanah Perkebunan Kentang - Khawas, Frafana Aripudin; Supatmi, Sri (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2023)
Potato is a horticultural commodity that plays an important role in realizing food security. Monitoring soil moisture in potato plant care plays an important role in potato growth and development. There are many obstacles faced in being able to monitor peatlands in Indonesia, so alternative surveillance methods are needed that can reach difficult locations. One of the approaches taken is a collaboration between Wireless Sensor Network (WSN) technology and IoT based on a microcontroller. The purpose of this study is to design a soil moisture sensor node by implementing IoT on a wireless system so that the system can be accessed remotely, and to compare accuracy, distance, and speed in tree and mesh topologies. The research method used in this research is descriptive analytical method with a qualitative approach. While in the application development process using the Wireless Sensor Network. This system is integrated with the IoT that uses ESP8266 as the processor of the sensor node that was created and uses the Raspberry Pi as a server for the entire system. The results showed that the system could be monitored remotely and made it easier for farmers to determine soil moisture. In the end, this application is present as an information medium to determine communication between sensor nodes in the agricultural world. This system also has an integrated feature with local agencies or regions to report soil moisture in potato plantations exceeding the specified humidity. The results of this study can be applied by farmers to facilitate the process of analyzing humidity with a remote system. Keywords :IoT, Mesh, Soil Moisture Sensor, Tree Network Topology, WSN